Let

f(x) = 2x3

and

g(x) = 3x2.

Find the value.

(g f)(−6)

(g f)(−6) = (No Response) seenKey

-47

 

by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

(g ∘ f)(x)=g(f(x));

f(-6)=2(-6)-3=-12-3=-15; g(-15)=3(-15)-2=-45-2=-47.

So (g ∘ f)(-6)=-47.

This can also be solved:

g(f(x))=3(2x-3)-2=6x-9-2=6x-11.

Put x=-6: g(f(-6))=6(-6)-11=-36-11=-47.

by Top Rated User (815k points)

Related questions

1 answer
1 answer
asked Mar 1, 2017 in Calculus Answers by lovelymath Level 2 User (1.9k points) | 1.0k views
1 answer
asked Aug 9, 2012 in Algebra 1 Answers by anonymous | 203 views
2 answers
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
85,994 questions
91,897 answers
2,229 comments
23,903 users